The Successful Treatment of a Cord Blood Transplant Recipient with Varicella Zoster Virus Meningitis, Radiculitis and Myelitis with Foscarnet - Shimizu, Ryo (Intern Med, 2017)
Infections of the central nervous system (CNS) with varicella zoster virus (VZV) is a rare occurrence after allogeneic hematopoietic stem cell transplantation. We herein report a case of VZV meningitis, radiculitis and myelitis that developed 8 months after cord blood transplantation, shortly after the cessation of cyclosporine and low-dose acyclovir. Although treatment with acyclovir did not achieve a satisfactory response, the patient was successfully treated with foscarnet. Our report indicates that VZV infection should be considered in allo-hematopoietic stem cell transplantation (HSCT) patients with CNS symptoms and that foscarnet may be effective for the treatment of acyclovir-resistant VZV infections of the CNS. The development of optimal prophylactic strategies and vaccination schedules may eradicate post-transplant VZV disease.